2005
DOI: 10.1007/s10869-004-2231-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects Of Recruitment Message Specificity On Applicant Attraction To Organizations

Abstract: We used the elaboration likelihood model from marketing research to explain and examine how recruitment message specificity influences job seeker attraction to organizations. Using an experimental design and data from 171 college-level job seekers, the results showed that detailed recruitment messages led to enhanced perceptions of organization attributes and person-organization fit. Perceptions of fit were found to mediate the relationship between message specificity and intention to apply to the organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
173
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(189 citation statements)
references
References 32 publications
9
173
0
7
Order By: Relevance
“…Consistent with earlier research (e.g., Roberson et al, 2005), we propose that person-reward fit perceptions will mediate the relationship between the specificity of compensation and benefits information and intention to pursue the job. More specific information will enable job seekers to better assess whether the offered reward package meets their expectations and needs.…”
Section: Person-reward Fit As a Mediator Of Compensation And Benefitssupporting
confidence: 83%
See 4 more Smart Citations
“…Consistent with earlier research (e.g., Roberson et al, 2005), we propose that person-reward fit perceptions will mediate the relationship between the specificity of compensation and benefits information and intention to pursue the job. More specific information will enable job seekers to better assess whether the offered reward package meets their expectations and needs.…”
Section: Person-reward Fit As a Mediator Of Compensation And Benefitssupporting
confidence: 83%
“…For instance, specific job information is likely to influence person-job fit whereas specific co-worker information might impact person-group fit. Along these lines, Roberson et al (2005) observed that more specific organizational information directly affected person-organization fit perceptions. Similarly, we propose that more specific reward information is likely to directly influence perceptions of person-reward fit.…”
Section: Person-reward Fit As a Mediator Of Compensation And Benefitsmentioning
confidence: 96%
See 3 more Smart Citations